1987
DOI: 10.1126/science.3299703
|View full text |Cite
|
Sign up to set email alerts
|

Localization, Secretion, and Action of Inhibin in Human Placenta

Abstract: Inhibin is a gonadal glycoprotein hormone that regulates the production of follicle-stimulating hormone (FSH) by the anterior pituitary gland and exhibits intragonadal actions as well. The present study shows that inhibin-like immunoreactivity (inhibin-LI) is present in cells of the cytotrophoblast layer of human placenta at term and in primary cultures of human trophoblasts. Human chorionic gonadotropin (hCG) stimulated secretion of inhibin-LI from these cultured placental cells. This effect was mimicked by 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
84
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(90 citation statements)
references
References 40 publications
5
84
0
1
Order By: Relevance
“…The β A protein is expressed in both inner and outer layers. The expressions of all these subunits are increased during the progression of pregnancy [75].…”
Section: Inhibins and Its Role In Tumourigenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The β A protein is expressed in both inner and outer layers. The expressions of all these subunits are increased during the progression of pregnancy [75].…”
Section: Inhibins and Its Role In Tumourigenesismentioning
confidence: 99%
“…This suggested that inhibin is a critical negative regulator of gonadal stromal cell proliferation, and it is antitumorigenic. The human placenta is a major source of plasma inhibin-like activity and placental cells in culture secrete these proteins [75]. The α-subunit and its mRNA are found in the cytotrophoblast region of the villi, whereas β B is expressed in the syncytial layer.…”
Section: Inhibins and Its Role In Tumourigenesismentioning
confidence: 99%
“…During pregnancy, the human trophoblast (2,3), fetal membranes (4) and decidua (5,6) express subunit mRNAs and immunoreactive proteins. Significant amounts of both proteins are secreted into the biological fluids of pregnancy (maternal and cord serum, coelomic and amniotic fluids) (7), and the feto-placental unit is the main source of circulating inhibin A and activin A (8).…”
Section: Introductionmentioning
confidence: 99%
“…Messenger RNA for inhibin a subunit has been identified in the syncytiotrophoblast and inhibin/activin b A and b B mRNAs have been identified in both cytotrophoblast and syncytiotrophoblast in the placenta (2). Immunocytochemical staining has also shown the presence of the a subunit, b A subunit and the b B subunit protein in syncytiotrophoblast (16,17) and the decidua (18).…”
Section: Introductionmentioning
confidence: 89%